O uso do blog na alfabetização - Soares, Raquel Pereira (2013)
This search presents a research carried out in a public school in the city of Uberlândia with 26 children enrolled in the 2nd year of elementary school. The object was analyze the impacts of a blog creation during the learning process of read and write at the literacy process; it was decided by the methodological principles of action research in order to achieve an instructional sequence that promotes changes in which subject analyzed, as well as the researcher, and generate data for analysis and understanding of the process of teaching and learning to read and write at school. Collection procedures and construction data throughout the process were observation, interview and action plan. The analysis was conducted from the interpretive method , based on the signs or indications of the data , the light of the ideas of Freinet (1974 , 1977) , Vygotsky (1988 , 2009) , Bajard (2002 , 2012) , Frank Smith (1991 ) Roger Chartier (1999) Bakhtin (2000) , Calil ( 2012, 2012 a, 2013 ) and Leontiev (1978). The research showed that students, subjects of this investigation, are involved in a process of teach and learn the writing and the reading supported by traditional methods linked in textbook, in prepared activities and the absence of production of texts. Children studied did not recognize the newspaper as a support for reading and do not use the computer to produce written. However, they were be motivated to write stories of themselves, using the computer for the purpose of producing leads and then post them on a blog, elaborated by them. The students become more interested in reading the newspaper and they recognized the computer like an instrument that helps and facilitates the process of writing texts. Furthermore, the teaching plan developed in this work, was directed to the child´s needs and it provided the children were been at activity as proposes the concept of Leontiev.